Характеристика трудового потенціалу Волинської області - Потапова, Алла Геннадіївна; Гоць, Оксана; Potapova, Alla H.; Hots, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2014)
Розкрито сутність понять "трудовий потенціа", "трудовий потенціал регіону". Охарактеризовано якісні та кількісні показники трудового потенціалу регіону. Досліджено внесок вітчизняних і зарубіжних вчених щодо визначення цих понять. Проаналізовано тенденції зміни трудового потенціалу області за 2009-2014 р.

The essence of the concepts of «working potential» and «working potential of the region» has revealed. Qualitative and quantitative indicators of working potential of the region have characterized. The contribution of domestic and foreign scholars on the definition of these concepts has investigated. The scientific approaches and methodological foundations for the study of working potential of the region have generalised. Providing features of working resources in Volyn region as a whole and its separate regions have examined. During 2009–2014 trends in working potential of the region have analyzed. The problems of rational use of working potential of the region, and the ways of overcoming these problems have detected. The measures for increasing the working potential in the Volyn region have proposed and the ways of further investigation of this concept have outlined.
Characteristics of the Working Potential in the Volyn Region
Keywords: регіон; трудовий потенціал; трудові ресурси; населення; працездатне населення; region; working potential; working resources; population; able-bodied population